Minimising the effects of manufacturing uncertainties in MEMS Energy harvesters - Hadi Madinei (Energy, 2018)
This paper proposes the use of an electrostatic device to improve the performance of MEMS piezoelectric harvesters in the presence of manufacturing uncertainties. Different types of uncertain parameters have been considered and randomised according to their experimentally measured statistical properties. It has been demonstrated that manufacturing uncertainty in MEMS harvesters results in a lower output power. Monte Carlo Simulation is used to propagate uncertainty through the MEMS mathematical model. It has been found that the uncertainty effects can result in two sets of samples. The first set of samples are those with resonance frequency higher than nominal values and the second set includes samples with resonance frequencies lower than the nominal value. The device proposed in this paper can compensate for the effects of variability in the harvester by tuning the resonance frequency to the nominal design. This device is composed of a symmetrical arrangement of two electrodes, which decrease the resonance frequency from its nominal value. However, achieving precise symmetrical conditions in the device on a micro-scale is not feasible. Therefore, the effects of an unsymmetrical arrangement due to manufacturing variability are also investigated. The device includes two arch-shaped electrodes that can be used to increase the resonance frequency.